Penguatan Sikap Tanggung Jawab Dalam Kegiatan Kepramukaan Di SMA Negeri 1 Canduang - Hudatul Hanani; Charles Charles; Iswantir M; Hamdi Abdul Karim (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research is motivated by several problems that the writer found at SMA Negeri 1 Canduang in scouting activities. Where in scouting activities there are still students who are not responsible, whereas in scouting the attitudes and actions of responsibility are clearly stated in the ninth Dasa Darma of scouting namely that scouts are responsible and trustworthy, but there are still students who follow scouts who do not carry out their responsibilities this study aims to find out the methods used by coaches in strengthening the attitude of responsibility of students, and what forms of attitude of responsibility are habituated in scouting. This type of research is field research of field research. The results of the study show that scout coaches use advice, prais, attention, reward and punishment methods in strengthening the attitude of responsibility of students who are still lacking.